Eugenol alleviates transmissible gastroenteritis virus-induced intestinal epithelial injury by regulating NF-κB signaling pathway - Wang, Kang; Chen, Daiwen; Yu, Bing; He, Jun; Mao, Xiangbing; Huang, Zhiqing; Yan, Hui; Wu, Aimin; Luo, Yuheng; Zheng, Ping; Yu, Jie; Luo, Junqiu (Frontiers in Immunology, 2022)
Increasing evidence supports the ability of eugenol to maintain intestinal barrier integrity and anti-inflammatory in vitro and in vivo; however, whether eugenol alleviates virus-mediated intestinal barrier damage and inflammation remains a mystery. Transmissible gastroenteritis virus (TGEV), a coronavirus, is one of the main causative agents of diarrhea in piglets and significantly impacts the global swine industry. Here, we found that eugenol could alleviate TGEV-induced intestinal functional impairment and inflammatory responses in piglets. Our results indicated that eugenol improved feed efficiency in TGEV-infected piglets. Eugenol not only increased serum immunoglobulin concentration (IgG) but also significantly decreased serum inflammatory cytokine concentration (TNF-α) in TGEV-infected piglets. In addition, eugenol also significantly decreased the expression of NF-κB mRNA and the phosphorylation level of NF-κB P65 protein in the jejunum mucosa of TGEV-infected piglets. Eugenol increased villus height and the ratio of villus height to crypt depth in the jejunum and ileum, and decreased serum D-lactic acid levels. Importantly, eugenol increased tight junction protein (ZO-1) and mRNA expression levels of nutrient transporter-related genes (GluT-2 and CaT-1) in the jejunum mucosa of TGEV-infected piglets. Meanwhile, compared with TGEV-infected IPEC-J2 cells, treatment with eugenol reduced the cell cytopathic effect, attenuated the inflammatory response. Interestingly, eugenol did not increase the expression of ZO-1 and Occludin in IPEC-J2 cells. However, western blot and immunofluorescence results showed that eugenol restored TGEV-induced down-regulation of ZO-1 and Occludin, while BAY11-7082 (The NF-κB specific inhibitor) enhanced the regulatory ability of eugenol. Our findings demonstrated that eugenol attenuated TGEV-induced intestinal injury by increasing the expression of ZO-1 and Occludin, which may be related to the inhibition of NF-κB signaling pathway. Eugenol may offer some therapeutic opportunities for coronavirus-related diseases.